1929
DOI: 10.1084/jem.49.4.615
|View full text |Cite
|
Sign up to set email alerts
|

Reactions of Rabbits to Non-Hemolytic Streptococci

Abstract: 1. Accompanying and following the evolution of a secondary reaction in the skin of rabbits after inoculation with suitable doses of certain non-hemolytic streptococci there quickly develops a general state of hypersensitiveness or allergy towards these streptococci. 2. This state is made evident by ophthalmic reactions following corneal inoculations, by much increased reactivity of the skin following intracutaneous reinoculations, and by lethal reactions, resembling tuberculin shock, following i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
9
0

Year Published

1929
1929
1953
1953

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 49 publications
(9 citation statements)
references
References 1 publication
0
9
0
Order By: Relevance
“…In previous papers it has been shown (1,2) that rabbits inoculated in practically any manner, except intravenously, with sufficiently large doses of certain non-hemolytic streptococci developed a condition of tissue hypersensitiveness. This was made evident by the occurrence of secondary reactions at the site of the primary inoculation, by the presence of corneal sensitivity after a certain period, by much larger reactions following intracutaneous re-inoculation than occur in normal animals inoculated with similar doses of culture; and finally by death of many of the animals following intravenous inoculation with amounts of culture well tolerated by normal rabbits.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In previous papers it has been shown (1,2) that rabbits inoculated in practically any manner, except intravenously, with sufficiently large doses of certain non-hemolytic streptococci developed a condition of tissue hypersensitiveness. This was made evident by the occurrence of secondary reactions at the site of the primary inoculation, by the presence of corneal sensitivity after a certain period, by much larger reactions following intracutaneous re-inoculation than occur in normal animals inoculated with similar doses of culture; and finally by death of many of the animals following intravenous inoculation with amounts of culture well tolerated by normal rabbits.…”
mentioning
confidence: 99%
“…The primary reactions of the 2 groups of animals also showed similar differences in consistency and size to those previously noted. These differences in size are brought out more strikingly by comparing their 1 The method of calculating these volumes is given in a previous paper (2). volumes as shown in Chart 2, where not only the greater initial size of the primary lesions, but also that of the secondary reactions in the normal animals is made evident.…”
mentioning
confidence: 99%
“…of 0.1 co. of a 1 : 100 dilution. The size of lesions produced is recorded in terms of cubic millimeter volume, estimated from measurements of two diameters and the height of each lesion, as described elsewhere (2).…”
Section: Methodsmentioning
confidence: 99%
“…It has been demonstrated that chronic low-grade infection, or numerous localized foci of inflammation induced in the rabbit by repeated minute inoculations with relatively avirulent (green or indifferent) streptococci, evoke a state of hypersensitivity to the bacteria (1,2). This hypersensitivity may be demonstrated by hyperreaction to minute doses injected intracutaneously, by an ophthalmic reaction following application of the bacteria to the scarified cornea, and by death in from 24 to 48 hours after intravenous doses tolerated by normal animals (2).…”
mentioning
confidence: 99%
“…The development and extent of sensitization was judged by means of the ophthalmic reaction (2). In addition, graded doses of bacteria were administered intradermally, and the size and course of the resulting lesions were observed daily for 72 hours (1). In the case of unsensitized controls, however, the intradermal inoculations were omitted, inasmuch as no increment of allergy, however slight, was considered desirable.…”
mentioning
confidence: 99%